2015
DOI: 10.3892/ijmm.2015.2237
|View full text |Cite
|
Sign up to set email alerts
|

Integrative genomic analyses of the RNA-binding protein, RNPC1, and its potential role in cancer prediction

Abstract: The RNA binding motif protein 38 (RBM38, also known as RNPC1) plays a pivotal role in regulating a wide range of biological processes, from cell proliferation and cell cycle arrest to cell myogenic differentiation. It was originally recognized as an oncogene, and was frequently found to be amplified in prostate, ovarian and colorectal cancer, chronic lymphocytic leukemia, colon carcinoma, esophageal cancer, dog lymphomas and breast cancer. In the present study, the complete RNPC1 gene was identified in a numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…The phylogenetic tree was obtained by using the maximum-likelihood (ML) method on the basis of the JTT amino acid sequence distance implemented in MEGA 5.1, and the reliability was evaluated by the bootstrap method with 1,000 replications (2432). …”
Section: Methodsmentioning
confidence: 99%
“…The phylogenetic tree was obtained by using the maximum-likelihood (ML) method on the basis of the JTT amino acid sequence distance implemented in MEGA 5.1, and the reliability was evaluated by the bootstrap method with 1,000 replications (2432). …”
Section: Methodsmentioning
confidence: 99%
“…The phylogenetic tree of Per a 10 and its homolog was obtained by the maximum-likelihood (ML) method on the basis of the JTT amino acid sequence distance implemented in MEGA 5.1, the reliability was evaluated by the bootstrap method with 1,000 replications (2832). …”
Section: Methodsmentioning
confidence: 99%
“…However, Ding et al 23 found that the relationship between expression of RBM38 and prognosis varied in different cancer tissues by bioinformatics analysis. In RCC clinical samples, we found that RBM38 was significantly down-regulated in RCC samples compared with adjacent non-tumor samples.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Recently, it has also found that the expression of RBM38 varied in different types of cancers by bioinformatics analysis. 23 However, expression and biologic functions of RBM38 in human RCC remain obscure. Moreover, there were few studies describing the relationship between the RBM38 expression and prognosis in patients who suffered from cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation